Intra-operative ventilator mechanical power as a predictor of postoperative pulmonary complications in surgical patients: A secondary analysis of a randomised clinical trial. Issue 1 (January 2022) - Karalapillai, Dharshi; Weinberg, Laurence; Neto A, Serpa; Peyton, Philip; Ellard, Louise; Hu, Raymond; Pearce, Brett; Tan, Chong O.; Story, David; O'Donnell, Mark; Hamilton, Patrick; Oughton, Chad; et al.
Abstract : BACKGROUND: Studies in critically ill patients suggest a relationship between mechanical power (an index of the energy delivered by the ventilator, which includes driving pressure, respiratory rate, tidal volume and inspiratory pressure) and complications. OBJECTIVE: We aimed to assess the association between intra-operative mechanical power and postoperative pulmonary complications (PPCs). DESIGN: Post hoc analysis of a large randomised clinical trial. SETTING: University-affiliated academic tertiary hospital in Melbourne, Australia, from February 2015 to February 2019. PATIENTS: Adult patients undergoing major noncardiothoracic, nonintracranial surgery. INTERVENTION: Dynamic mechanical power was calculated using the power equation adjusted by the respiratory system compliance ( C RS ). Multivariable models were used to assess the independent association between mechanical power and outcomes. MAIN OUTCOME MEASURES: The primary outcome was the incidence of PPCs within the first seven postoperative days. The secondary outcome was the incidence of acute respiratory failure. RESULTS: We studied 1156 patients (median age [IQR]: 64 [55 to 72] years, 59.5% men). Median mechanical power adjusted by C RS was 0.32 [0.22 to 0.51] (J min −1 )/(ml cmH2 O −1 ). A higher mechanical power was also independently associated with increased risk of PPCs [odds ratio (OR 1.34, 95% CI, 1.17 to 1.52); P < 0.001) and acute respiratory failure (OR 1.40, 95% CI, 1.21 to 1.61; P < 0.001). CONCLUSION: In patients receiving ventilation during major noncardiothoracic, nonintracranial surgery, exposure to a higher mechanical power was independently associated with an increased risk of PPCs and acute respiratory failure. TRIAL REGISTRATION: Australia and New Zealand Clinical Trials Registry no: 12614000790640. Abstract : Supplemental Digital Content is available in the text